New design of spectral amplitude coding in OCDMA with zero cross-correlation - Anuar, Mat Safar; Syed Alwee Aljunid, Syed Junid; N. M., Saad; S. M., Hamzah (Elsevier B.V. (Imprint: NORTH-HOLLAND), 2009)
Link to publisher's homepage at http://www.elsevier.com